Relationship between the three dimensions of institutes required for entrepreneurship development - Saurabh Sonkar; Ashoke Kumar Sarkar (Journal of Sustainable Tourism and Entrepreneurship, 2020)
Purpose: The study was conducted to formulate the relationship between the three dimensions of institutes, namely cognitive, regulative and, normative dimensions of institutes. The model was formulated using SmartPLS 3. Research Methodology: In this study, the Five-point Likert scale was used and the data were collected from postgraduate students in two states of Uttar Pradesh and Jharkhand. SmartPLS 3 was used to formulate the model and establish the relationship between the three dimensions of institutes. Results: There exists a positive relationship between "Cognitive dimension and normative dimension"; "Regulative dimensions and Cognitive dimensions; and between Regulative dimensions and Normative dimensions" respectively of institutes. Limitations: Study is conducted on a small sample of 100 postgraduate students from two states of India namely Jharkhand and Uttar Pradesh which may decrease the reliability of the study. Contribution: In this study, a relationship is established by using smart PLS 3 between the three dimensions of institutes required for entrepreneurship development with the help of Likert scale developed based on previous studies which can help in measuring the country institutional profile and provide the base for studying the role of these dimension of the institute in entrepreneurial intention growth among the postgraduate students in states of India.